Expressive Writing Therapy through Online and Offline Media to Reduce Nomophobia Level during the Pandemic Covid-19 - Arinda Ayudya Putri Riyanto; Laila Rahmania Adjani; Serly Hanan Safirah,; Anisa Fitriani (Universitas Ahmad Dahlan, 2022)
Everyone needs a smartphone during the pandemic, which makes people use online communication more. However, inappropriate and excessive use can cause problems, such as nomophobia. This study aimed to determine the effect of expressive writing therapy in reducing the level of nomophobia. The research method uses a quasi-experimental design with a pretest-posttest design with a control group. The sampling technique used was purposive sampling with 23 male and female subjects aged 19-21 years who had moderate to high levels of nomophobia—collecting data through observation, interviews, and the Nomophobia Questionnaire (NMP-Q). Expressive writing therapy was given to the experimental group for five sessions through online and offline media. Data analysis using a quantitative approach with the Mann-Whitney statistical test obtained a significance of p = 0.0425 (P <0.05), so it can be concluded that there is a significant difference in nomophobia scores between the control and experimental groups after being given expressive writing therapy. The results of the qualitative analysis showed that the subject experienced nomophobia due to unpleasant past experiences, parenting and environmental demands, loneliness, and work needs. The decrease in nomophobia scores was influenced by various new understandings gained after receiving expressive writing therapy.